1971
DOI: 10.1590/s0034-89101971000200008
|View full text |Cite
|
Sign up to set email alerts
|

Sôbre os trabalhos da campanha de combate à esquistossomose no Estado de São Paulo, Brasil

Abstract: Foi demonstrado que a esquistossomose está em fase de expansão no Estado de São Paulo, o que vem sendo comprovado através da descoberta de novos focos ativos em municípios onde já havia sido assinalada; da verificação de seu recrudescimento a cada ano pelo registro de novos casos autóctones e, ainda pela observação de focos ativos no início de sua instalação, isto é, captura de planorbídeos naturalmente infectados pelas cercárias do Schistosoma mansoni em localidades onde até o momento não se constatou qualque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In the year 1975, the discovery of six cases of schistosomiasis mansoni in the municipality was announced by Piza (1976). However, Corrêa et al (1962) and Ramos and Piza (1971) had already found planorbid vectors in that municipality. Even though the collection of infected snails was at that time a requisite for the transmission of Schistosoma mansoni in a site to be admitted, it is presumable that cases of schistosomiasis in Bananal had been known earlier to the personnel of the Campanha de Combate à Esquistossomose (CACEsq) -Campaign to Combat Schistosomiasis -subsequently known as Superintendência de Controle de Endemias, Sucen (Superintendency of Control of Endemic Diseases).…”
mentioning
confidence: 91%
“…In the year 1975, the discovery of six cases of schistosomiasis mansoni in the municipality was announced by Piza (1976). However, Corrêa et al (1962) and Ramos and Piza (1971) had already found planorbid vectors in that municipality. Even though the collection of infected snails was at that time a requisite for the transmission of Schistosoma mansoni in a site to be admitted, it is presumable that cases of schistosomiasis in Bananal had been known earlier to the personnel of the Campanha de Combate à Esquistossomose (CACEsq) -Campaign to Combat Schistosomiasis -subsequently known as Superintendência de Controle de Endemias, Sucen (Superintendency of Control of Endemic Diseases).…”
mentioning
confidence: 91%